Skewness preferences in choice under risk - Ebert, Sebastian; Karehnke, Paul (SSRN, 2021)
Skewness preferences—preferences toward low-probability, high-impact risks—are crucial determinants of economic behavior. This paper defines first- and higher-order skewness preferences and shows that the order of skewness preference captures the importance of skewness relative to mean and variance. While leading theories of choice under risk largely agree on the direction of skewness preference, they disagree on the order. In expected utility, skewness-seeking cannot be first-order—an impossibility result—which motivates the use of behavioral theories in economic modeling